2011
DOI: 10.1128/jb.05939-11
|View full text |Cite
|
Sign up to set email alerts
|

Decay of a Model mRNA in Bacillus subtilis by a Combination of RNase J1 5′ Exonuclease and RNase Y Endonuclease Activities

Abstract: The involvement of the recently characterized 5 exonuclease activity of RNase J1 and endonuclease activity of RNase Y in the turnover of ⌬ermC mRNA in Bacillus subtilis was investigated. Evidence is presented that both of these activities determine the half-life of ⌬ermC mRNA.The 260-nucleotide (nt) ⌬ermC mRNA ( Fig. 1A) has served as a useful model for determining the effects of structural and translational elements on mRNA stability in Bacillus subtilis (1,16,17,20). The involvement of the essential RNase J1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…By contrast, the turnover of trp leader mRNA, which is dependent upon endonucleolytic cleavage by RNase J1, occurred irrespective of the phosphorylation status of the mRNA 5′ end (Deikus and Bechhofer, 2011). Interestingly, RNase Y‐dependent endonucleolytic decay also occurs independently of the presence of either a mono‐ or a triphosphate at the 5′ end of the ermC mRNA (Yao et al ., 2011). The finding of the RppH pyrophosphorylase activity in B. subtilis is intriguing, but its significance for overall mRNA decay remains to be demonstrated.…”
Section: Additional Players In Rna Degradation In B Subtilismentioning
confidence: 99%
“…By contrast, the turnover of trp leader mRNA, which is dependent upon endonucleolytic cleavage by RNase J1, occurred irrespective of the phosphorylation status of the mRNA 5′ end (Deikus and Bechhofer, 2011). Interestingly, RNase Y‐dependent endonucleolytic decay also occurs independently of the presence of either a mono‐ or a triphosphate at the 5′ end of the ermC mRNA (Yao et al ., 2011). The finding of the RppH pyrophosphorylase activity in B. subtilis is intriguing, but its significance for overall mRNA decay remains to be demonstrated.…”
Section: Additional Players In Rna Degradation In B Subtilismentioning
confidence: 99%
“…Interestingly, this complex resembles the E. coli degradosome. RNase Y was proposed to be involved in the initiation of riboswitch turnover (Shahbabian et al ., 2009; Bruscella et al ., 2011), to play a key role in the initiation of RNA decay of selected transcripts (Yao and Bechhofer, 2010; Yao et al ., 2011) as well as rRNA and different mRNA in aging spores (Segev et al ., 2012). In vitro assays have shown that the endoribonuclease activity of RNase Y requires RNA with a 5′ monophosphorylated end (Shahbabian et al ., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In an alternative pathway RNA decay starts directly with an endonucleolytic cleavage by RNase J1. After the first events, RNA decay continues with 5′ to 3′ exoribonuclease activity by RNase J1 and 3′ to 5′ exoribonuclease activity by PNPase (Yao and Bechhofer, 2010; Yao et al ., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The initial breakdown products are then degraded further by exonucleases such as polynucleotide phosphorylase, RNase II or its homologue RNase R (Figure 4). In Gram-positive bacteria, RNases J1, J2 and Y are the functional equivalents of RNase E and RNase G, but have no sequence homology to these proteins (Yao et al, 2011). See also: mRNA Stability Multiprotein Complexes that Degrade mRNA mRNA decay is carried out by multiprotein complexes in bacteria It now appears that in many prokaryotes multiprotein complexes that contain several enzymes involved in the decay of mRNAs serve to degrade a large fraction of the cells' mRNAs.…”
Section: Mrnas Are Degraded By a Variety Of Ribonucleasesmentioning
confidence: 99%